False-positive technetium-99m methylene diphosphonate bone scan activity in the orbit in a patient with a history of breast carcinoma - Sarah Bonnet; Joel Palko (World Journal of Nuclear Medicine)
Metastasis of breast carcinoma to the orbit is an uncommon entity and carries a poor prognosis. This case report presents false-positive technetium-99m methylene diphosphonate activity in the right orbit of a patient with a history of a primary breast neoplasm. Orbital computed tomography imaging was obtained to further characterize the radiotracer uptake identified on the bone scan and demonstrated diffuse right globe intraocular calcifications secondary to degenerative intraocular changes. A brief literature review of orbital metastasis from breast carcinoma and causes of intraocular calcification in the context of chronic vision loss are provided.